Corporate Criminal Liability in Jordan, Australia, and Indonesia: A Comparative Analysis of Doctrines and Recent Developments - Emiliya Febriyani; Jamin Ginting; Basuki Rekso Wibowo (Journal of Law and Policy Transformation, 2025)
This study analyzes the development of corporate criminal liability in Jordan, Australia, and Indonesia through a comparative doctrinal approach, focusing on the shift from the traditional identification doctrine toward models that attribute criminal fault to corporate culture. The research applies a normative legal method combined with comparative legal analysis, examining the Jordanian Penal Code, the Australian Criminal Code Act 1995 (Cth) and the Australian Law Reform Commission Report No. 136 (2020), Law No. 1 of 2023 on the New Indonesian Criminal Code (KUHP), and Supreme Court Regulation No. 1 of 2023, alongside scholarly literature on identification doctrine, vicarious liability, strict liability, and corporate culture theory. The findings show that Jordan retains a classical identification-based model, holding corporations liable only when fault can be linked to individuals acting as the “directing mind and will.” Australia has adopted the most advanced framework through Section 12.3 of the Criminal Code, which attributes fault based on corporate culture and is strengthened by proposals for system-of-conduct offences. Indonesia occupies a transitional position: although the Law No. 1 of 2023  formally recognizes corporations as criminal subjects, its fault-attribution structure remains hybrid, and organizational fault is only expressly acknowledged sectorally through Supreme Court Regulation No. 1 of 2023. The study concludes that effective corporate criminal liability depends on a legal system’s capacity to conceptualize fault as systemic failure rather than individual wrongdoing.